ANALISIS USAHA BUDIDAYA IKAN NILA (Oreochromis niloticus) DALAM KERAMBA JARING APUNG DI PT. RAMA JAYA MAHAKAM DESA LOA KULU KOTA KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Hesty Nurita Putri; Fitriyana Fitriyana; Qoriah Saleha (LPPM Politeknik Pratama, 2022)
The purposes of the study are to determine the income. for freshwater fish farming in floating net cages (KJA) at PT. Rama Jaya Mahakam. This research was conducted from January 2020 to June 2022. The sample determination was based on the Purposive Sampling method, with 1 respondent, namely the business owner, The primary data was obtained from business owners by means of interviews using a list of questions. Data were analyzed by quantitative analysis. The results of the analysis showed that the income was IDR. 212.588.090/year.